Harmonization of accounting in the process of globalization of economic activities - Georgescu, Floarea; Ionescu, Cicilia (Journal of Economic Development, Environment and People, 2014)
Abstract. Once with the Romania adhering at the European Union the public accounting system was transformed and adapted according to the requirements imposed by the international public sector accounting standards (IPSAS).This fact had imposed the appearance of legislative norms and provisions adapted to the actual requirements, by taking into account the growing and complex level of economic activities where the irreversible process of globalization takes place. The changes due to the economic politics, especially the new configuration of the international economic relations, relations characterized by an intense and irreversible process of globalization, have conducted to the implementation of a unitary and uniform legislation, particularly for the member states of EU. The accounting reform has begun through the harmonization of legislation according to the requirements and provisions of International Accounting Standards and European Directives. The ampleness and the rapid rhythm of informational society’s development have implicitly leaded to the development of accounting information’s importance and dimension. The decisive role of the accounting information had conducted to the accentuated growth of the interest, manifested at all informational society’s level, from the development of activities in financial and economical domain point of view. The accounting normalization process imposed the development of norms and provisions necessary to the drawing up of accounting documents, by defying methods and a specialized terminology, applied in the activity of entities and accounting specialists.